Teacher Professional Development in Modern Islamic Boarding School: A Systematic Literature Review - Bunyamin Bunyamin; Fathur Rokhman; Nina Oktarina (Proceedings of International Conference on Science, Education, and Technology, 2026)
Teacher professional development (TPD) has become increasingly important in modern Islamic boarding schools (pesantren) in response to educational transformation, technological advancement, and the growing demand for high-quality learning. Teachers are expected to possess not only pedagogical competence but also digital literacy, professional commitment, and the ability to integrate Islamic values into educational practices. This study aims to synthesize recent research on teacher professional development in modern pesantren and identify key factors contributing to teacher competence enhancement and educational innovation. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Fifteen peer-reviewed studies published between 2019 and 2025 were selected based on predefined inclusion criteria and analyzed using thematic synthesis. The findings revealed five dominant themes influencing the effectiveness of teacher professional development: enhancement of pedagogical competence, development of digital literacy and technological adaptation, integration of Islamic values, collaborative professional learning, and leadership support. The review indicates that sustainable and context-sensitive professional development programs contribute significantly to improving instructional quality, teacher professionalism, and educational innovation in pesantren. Based on these findings, an integrative teacher professional development framework is proposed, combining pedagogical innovation, digital literacy, Islamic values integration, collaborative learning communities, and reflective supervision. This study contributes to the growing discourse on teacher professionalism in Islamic education and provides practical recommendations for policymakers, educational leaders, and pesantren administrators in designing sustainable professional development programs.